Inside Cover: Strong, Thermally Superinsulating Biopolymer–Silica Aerogel Hybrids by Cogelation of Silicic Acid with Pectin (Angew. Chem. Int. Ed. 48/2015). Issue 48 (19th October 2015) - Zhao, Shanyu; Malfait, Wim J.; Demilecamps, Arnaud; Zhang, Yucheng; Brunner, Samuel; Huber, Lukas; Tingaut, Philippe; Rigacci, Arnaud; Budtova, Tatiana; Koebel, Matthias M.
Abstract : The biopolymer pectin is readily extracted from apple peel and can be used as an efficient reinforcing agent for silica aerogels. In their Communication on page 14282 ff., M. M. Koebel, T. Budtova et al. present a one‐pot route to monolithic, thermally superinsulating, hybrid silica aerogels through cogelation of pectin and silicic acid, post‐processing, and supercritical drying. This study opens up new perspectives for the synthesis of high‐performance hybrid aerogels.